VALUE ADDED TAX RATE CHANGE: EFFECTS ON INFLATION RATE AND GOVERNMENT BORROWING IN NIGERIA - Afolayan, Segun Matthew; Okonkwo, Ikeotuonye Victor; Okaro, Celestine Sunday (Journal of Contemporary Issues in Accounting, 2021)
The tax revenue to the Nigerian government especially the indirect tax revenue has been observed to be inadequate for growing needs of government. The Federal Government has therefore enacted the Finance Act 2020 introducing changes to the Companies Income Tax Act, Value Added Tax Act, Petroleum Profits Tax Act, Personal Income Tax Act, Capital Gains Tax Act, Customs and Excise Tariff Etc. (Consolidation) Act and Stamp Duties Act. Value Added Tax (VAT) rate has changed from 5% to 7.5% with effect from 1 February 2020. The Federal Inland Revenue Service has also issued a clarifying circular on the operation procedure and exemptions. There has been a barrage of argument that higher tax rates especially the new VAT rate are needed to bring in desperately needed revenue to government as its previous 5% rate’s impact seems neither significant on national revenue nor reduced government reliance on loans and foreign aids. Others still fear that the increase will adversely affect other macroeconomic variables especially inflation rate. The questions are: What effect would increase in VAT rate has on inflation rate in Nigeria? How would the new VAT rate minimize the volume of Nigerian government borrowing? This work therefore assessed the effect of an increase in VAT rate on inflation rate in Nigeria; and the relationship between Value Added Tax and Nigeria’s total debt outstanding. The work hypothesized that: VAT rate increase would not significantly cause a change in inflation rate in Nigeria; and there is no significant relationship between VAT revenue and Nigeria’s total debt outstanding. The study adopted the ex post facto research method using a regression technique (Koyck Model) which rides on adaptive expectation hypothesis. Data were sourced from Federal Inland Revenue Services (FIRS) and Central Bank of Nigeria (CBN) statistical bulletins. The findings showed that increase in VAT rate does not guarantee more revenue that will bring about significant reduction in government borrowing but could worsen inflation rate in Nigeria. The paper concluded that general paucity of patriotism among citizens tend to frustrate even seeming good policies of the government. The government should have the political will to entrench culture of transparency and accountability; impose VAT on foreign goods that have local substitutes, and all luxury goods; work towards institutionalizing the tax institution such that no person should influence the tax policies selfishly.